Peranan Wanita dalam Pengukuhan Akidah Umat Islam - Saari, Che Zarrina; Borhan, Joni Tamkin (Jurnal Usuluddin, 2006)
At the time of the dawn of Islam, women all over the world were degraded, subjected and without any rights and some of them were considered as men-entities. Since the beginning of the industrial revolution, they have been asserting their rights in the Western countries and have been given certain political and economic rights. But more than fourteen hundred years ago, Islam recognised womens position and gave them rights, roles and privileges which are not enjoyed by women in other societies. The overall position of women is honourable and noble in the sight of Allah SWT as well as in the eyes of Islamic society. This article explains about the role of women in educating their children and strengthening their aqidah and what is the method can be used in achieving this aims.